2019
DOI: 10.1038/s41598-019-46132-9
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA signature refine response prediction in CML

Abstract: microRNAs (miRs) dysregulation have emerged as a crucial step in tumorigenesis, being related with cancer development, progression and response to treatment. In chronic myeloid leukaemia (CML), the resistance to tyrosine kinase inhibitors (TKI) is responsible for treatment failure and could be linked to changes in miRs expression. This work aimed to correlate the expression levels of 3 miRs, miR-21, miR-26b and miR-451, with response to TKI treatment in CML patients. miR-451 levels at diagnosis were significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 38 publications
2
25
0
Order By: Relevance
“…However, by our approach we were able to identify miR-142-5p as most robustly expressed miRNA showing significant expression differences in both, peripheral blood and bone marrow samples. Although the expression differences were modest, they could substantially influence cellular processes [74]. This is also supported by the recent study of Alves et al in CML patients, which described slight miRNA expression differences between TKI non-responders and responders at diagnosis that became more pronounced after six and twelve months of therapy [75].…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…However, by our approach we were able to identify miR-142-5p as most robustly expressed miRNA showing significant expression differences in both, peripheral blood and bone marrow samples. Although the expression differences were modest, they could substantially influence cellular processes [74]. This is also supported by the recent study of Alves et al in CML patients, which described slight miRNA expression differences between TKI non-responders and responders at diagnosis that became more pronounced after six and twelve months of therapy [75].…”
Section: Discussionmentioning
confidence: 61%
“…However, by our approach we were able to identify miR-142-5p as most robustly expressed miRNA showing significant expression differences in both, peripheral blood and bone marrow samples. Although the expression differences were modest, they could substantially influence cellular processes [ 74 ]. This is also supported by the recent study of Alves et al .…”
Section: Discussionmentioning
confidence: 99%
“…A few studies point out the involvement of immune cells for the control of TFR. It has been demonstrated that there is an increase in natural killer (NK) cells and a decrease in CD3 + CD8 + CD62L + cells in patients in whom imatinib was discontinued (STOP-IM) compared to CML patients taking imatinib in complete molecular remission (CMR), which was positively associated with CMR [ 124 ]. Another trial (EURO-SKI) revealed a higher rate of TFR in CML patients with a higher percentage of NK, but not B- or T-cells.…”
Section: Treatment Free Remissionmentioning
confidence: 99%
“…However, the relevance between miR-21 and TKI resistance in CML has rarely been reported. In a study that predicted which patients would achieve the optimal response with TKIs, miR-21 expression levels were found to be the highest in patients who did not respond optimaliy after 6 and 12 months of treatment [23]. In this case, miR-21 may be a novel therapeutic strategy to reverse TKIs resistance in…”
Section: Introductionmentioning
confidence: 95%